Usos tradicionales de la flora medicinal y mágico religiosa en el departamento del Quindío (2017)
It was carried out a study about the uses of medicinal and magical religious plants, for this purpose there were developed two types of surveys which were implemented in plants experiments in the urban area of each one of the 12 municipalities in the department of Quindío. For the current study we applied 101 surveys in order to evaluate the importance of these: through the value of use and level of significance index TRAMIL. 245 species are reported for medicinal purposes from which a 68% are not reported in the vademecum, and 111 are reported for magical religious purposes. The results obtained file the plants of greater cultural importance, in both medicinal and magical religious purposes. Later, there were obtained 11 species of medicinal plants: Moringa oleifera (Moringa), Calendula officinalis (Calendula), Aloe vera (Sábila), Cassia angustifolia (Sen) Hispanic sage (Chia), Pneumus boldus molina (Boldo), Rosmarinus officinalis (Romero), Chamomilla recutita (Manzanilla) Eucalyptus globulus (Eucalyptus), Mentha viridis (Yerbabuena) and Aloysia triphylla (Cidron) and in the magical religious area 9 species were obtained: Koanophyllon villosum (Abrecaminos), Labradorum anagyroides (Lluvia de oro), Peperomia nitida (Quereme), Desmodium incanum (Pega pega), Ruta graveolens (Ruda), Peperomia fraserri (Sigueme), Cymbopogon nardus (Citronella), Salvia officinalis (Salvia) and Artemisia vulgaris (Altamisa). The outlets of medicinal plants are distributed in naturism stores, drugstores and traditional herbalists, within this, magical religious plants are included.